2020
DOI: 10.5933/jkapd.2020.47.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Association between Parenting Styles and Dental Caries in Preschool Children

Abstract: This study aimed to evaluate the relationship between parenting styles and childhood dental caries using a sample of 3 to 6 years old children in Korea.The subjects were 158 children aged 3 to 6 years old and their parents in Korea. The parenting styles were divided into three groups (authoritative, authoritarian, and permissive) using a translated version of the Parenting Styles and Dimensions Questionnaire (PSDQ).Among the 353 parents/child dyads, 158 questionnaires were returned. Authoritative parenting sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
2
Order By: Relevance
“…On the contrary, the results of our study revealed a lower prevalence of authoritative parents than what was found by (Lee et al, 2020) in South Korea and by (Alagla et al, 2021) in Saudi Arabia, where the authoritative parenting style was dominating, while the prevalence of permissive and authoritarian parents was higher in our study than what was found by (Lee et al, 2020) where they have very low rates of permissive and authoritarian parents. However, in Saudi Arabia the authoritarian style didn't exist they only have two parenting styles and this might be because of the shift in parenting styles worldwide as denoted by (Alagla et al, 2021).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, the results of our study revealed a lower prevalence of authoritative parents than what was found by (Lee et al, 2020) in South Korea and by (Alagla et al, 2021) in Saudi Arabia, where the authoritative parenting style was dominating, while the prevalence of permissive and authoritarian parents was higher in our study than what was found by (Lee et al, 2020) where they have very low rates of permissive and authoritarian parents. However, in Saudi Arabia the authoritarian style didn't exist they only have two parenting styles and this might be because of the shift in parenting styles worldwide as denoted by (Alagla et al, 2021).…”
Section: Discussioncontrasting
confidence: 91%
“…Regarding parenting style and its effect on children's caries experience, our results showed that there was no significant relation between them as in (Arrepia et al, 2019) and (Lee et al, 2020). The non-significant association between dental caries and family impacts in our study could be explained by the low number of children suffering from severe dental caries.…”
Section: Discussioncontrasting
confidence: 55%